PEMBELAJARAN PENDIDIKAN JASMANI ADAPTIF DALAM JARINGAN (DARING) BAGI ANAK TUNANETRA DI SLBN TAMANSARI KOTA TASIKMALAYA - Rosyidatunnisa, - (2021)
With the arrival of covid 19 in Indonesia, with the number of positively affected patients with COVID-19 increasing, a policy has emerged that was given by the government, namely to organize distance learning and advise students to study from their respective homes. This study aims to find out about adaptive physical education learning in the network (online) for blind children at SLBN Tamansari Tasikmalaya city. The method used is descriptive qualitative method with data collection techniques in the form of interviews, observations and documentation studies. The subjects of this study consisted of one teacher of adaptive physical education and one teacher of the special junior high school class. Testing the validity of the data is done by using triangulation. The results showed that the preparation of learning programs such as semester programs, annual lesson plans for the implementation of adaptive physical education students was not required to be made, because the teacher focused on making learning materials that had to be adapted to the conditions of students. The obstacles experienced in learning adaptive physical education online are caused by unstable networks and also students who are carrying out other activities during learning. Implementation of adaptive physical education learning in the network for blind children, the teacher stated that in the implementation of the learning process it was only carried out by class teachers. It is recommended to continue to monitor the implementation of adaptive physical education learning online, to build better communication for readiness for learning implementation. Parents are expected to continue to guide and assist their children in carrying out the online learning process. Keywords: blind, adaptive physical education, online